Biogeographic Events Are Not Correlated with Diaspore Dispersal Modes in Boraginaceae - Chacón, Juliana; Luebert, Federico; Weigend, Maximilian (Frontiers in Ecology and Evolution, 2017)
Long-distance dispersal seems to be the main biogeographic event responsible for intriguing distribution patterns in plant groups in which sister taxa are separated by thousands of kilometers of distance across oceans and continents. The biotic and abiotic mechanisms behind such dispersal events are poorly understood and many attempts have been made to explain how plants can manage to disperse and survive these long journeys. The biogeographic history of Boraginaceae, a subcosmopolitan plant family with many disjunct clades, is here addressed and analyzed in the context of the different dispersal modes exhibited by the species. The lack of a clear pattern between the main dispersal events in Boraginaceae and the phylogenetic distribution of the dispersal modes indicates that no single dispersal mechanism can be associated with the events of dispersal in the family. Moreover, adaptations to different dispersal agents and unassisted dispersal modes in some clades might have promoted the diversification of Boraginaceae in various habitats across several continents. Our study reveals that long-distance dispersal is a very complex process that needs to be analyzed in the context of climatic and environmental changes and the response of plants and their dispersal vectors to these variable conditions.